Design and Analysis of Nozzle Exit Area for Science Technology Engineering and Mathematics (STEM) Based Solid Rocket Propellant - Rahim, Muhammad Fadhli Hairi; Ariffin, Ahmad Hamdan (Progress in Aerospace and Aviation Technology, 2025)
The performance of a solid rocket propulsion system depends strongly on the geometric characteristics of its convergent–divergent (C-D) nozzle, particularly the exit area that determines the expansion of exhaust gases and the resulting thrust. This study investigates three C-D nozzle configurations with identical inlet and throat diameters using Computational Fluid Dynamics (CFD) simulations in ANSYS Fluent. Each nozzle was analyzed in terms of static pressure, temperature distribution, and velocity magnitude under the same operating conditions. The results indicate that all designs achieve choked flow at the throat, with peak velocities entering the supersonic regime. However, significant differences were observed downstream. Design B exhibits the most favorable flow characteristics, including a smooth pressure reduction of approximately 60–70% from inlet to throat, a uniform temperature decrease of about 25–30% across the divergent region, and the highest, most uniform exit velocity with minimal backflow. Designs A and C, in contrast, display irregular pressure recovery and non-uniform temperature and velocity gradients, indicating potential inefficiencies and localized separation. Overall, the findings confirm that nozzle contour geometry has a substantial effect on expansion efficiency, and the optimized configuration demonstrates strong potential for improving thrust and specific impulse in STEM solid rocket applications.